Pattern of Cytology and Lung Biopsy Findings in Patients with Chronic Inflammation, Atypical Lesions and Cancer by Age Group - Chakramurty, Alendra; Bahri, Syamsul (Newinera Publisher, 2025)
Lung diseases, both non-neoplastic such as chronic pneumonia and neoplastic such as lung cancer, have similar clinical characteristics so that they are difficult to differentiate. Cytological studies and lung biopsies are important diagnostic methods in determining the pattern of findings between the two conditions, especially when related to the patient's age group. This study used a retrospective descriptive design to analyze patterns of cytology and lung biopsy findings in patients with chronic lung inflammation, inflammation with atypical cells, and lung cancer based on age group. Data was taken from patient medical records at Sidawangi Hospital, West Java, in the period July 2024 – January 2025. Of the 109 patients who met the inclusion criteria, 87 patients were diagnosed with chronic pneumonia and 36 patients with lung cancer. The results showed that the average age of lung cancer patients was 62.78 years, while chronic lung inflammation patients had an average age of 56.12 years. Patients with atypical lesions had a mean age of 47.82 years. These findings indicate differences in cytology and lung biopsy patterns between chronic pneumonia and lung cancer patients, with a higher prevalence of lung cancer in the elderly.